Overexpression of miR-221 in sudden death with cardiac hypertrophy patients. Issue 6 (June 2018) - Kakimoto, Yu; Tanaka, Masayuki; Hayashi, Hideki; Yokoyama, Keiko; Osawa, Motoki
Abstract: Background: Cardiac hypertrophy is a well-known risk factor for heart failure and sudden cardiac death (SCD). On the other hand, physiological cardiac hypertrophy is often observed in young healthy men, and it is difficult to predict SCD in cardiac hypertrophy subjects who do not show symptoms of heart failure. MicroRNAs (miRNAs) widely regulate biological activity and play pivotal roles in heart failure progression. In this study, we investigated whether miRNA expression is altered in SCD with cardiac hypertrophy (SCH). Methods: Cardiac tissues were sampled at autopsy from SCH patients, compensated cardiac hypertrophy (CCH) subjects who died of causes other than heart failure, and control cases without cardiac hypertrophy or heart failure. After histopathological examination, we performed deep sequencing and quantitative PCR of cardiac miRNAs. Results and discussion: Although SCH and CCH showed indistinguishable histological features, their miRNA expression signatures were distinct. Among the 240 miRNAs stably detected in the heart, 8 were differentially expressed between SCH and CCH. Specifically, miR-221 increased in SCH compared to CCH and control cases. The significant elevation of cardiac miR-221 in SCH patients is correlated with lethal outcomes. Thus, our results indicate that an elevated miR-221 level is potentially associated with an increased risk of SCD in subjects with cardiac hypertrophy.